Necrotizing Craniocervical Soft Tissue Infections: Clinical Experience and Personal Considerations. (4th December 2012) - Gallo, Stefania; Karligkiotis, Apostolos; Lenzi, Riccardo; Castelnuovo, Paolo; Dallan, Iacopo
Abstract : Necrotizing cervical soft tissue infections (NCSTIs) are devastating uncommon clinical entities that are often life threatening. We report two patients suffering from NCSTI and treated at our institution. Diagnosis of NCSTI has been confirmed histologically and surgically. Both patients were managed with very aggressive treatment (medical and surgical) and survived with minimal morbidity. Early diagnosis and aggressive, multimodality treatment can reduce mortality and morbidity rates. Thoracic and mediastinal involvement requires appropriate management. A strong clinical suspicion remains one of the most important aspects of the management of such shattering conditions.